2017
DOI: 10.1002/jcc.24760
|View full text |Cite
|
Sign up to set email alerts
|

Modeling adsorbate‐induced property changes of carbon nanotubes

Abstract: Because of their potential for chemical functionalization, carbon nanotubes (CNTs) are promising candidates for the development of devices such as nanoscale sensors or transistors with novel gating mechanisms. However, the mechanisms underlying the property changes due to functionalization of CNTs still remain subject to debate. Our goal is to reliably model one possible mechanism for such chemical gating: adsorption directly on the nanotubes. Within a Kohn-Sham density functional theory framework, such system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…Clar demonstrated that the valence bond structure with the most aromatic sextets best models the reactivity of polyaromatic hydrocarbons and that structures possessing only aromatic sextets are especially stable, Figure . It has been shown that structures with the maximum amount of aromatic sextets for a given chirality and number of carbon atoms best describe the reactivity and geometry of CNTs and CNT–reactant studies. Accordingly, computational investigations employing “straight cut” CNT samples might misrepresent the reactivity of the studied model, which might be the source of some inconsistencies in published results on CNT–analyte interactions. For detailed discussions on the Clar sextet rule in CNTs, we refer the interested reader to key studies by Matsuo et al, Baldoni et al, , and Ormsby et al , …”
Section: Introduction and Scopementioning
confidence: 99%
“…Clar demonstrated that the valence bond structure with the most aromatic sextets best models the reactivity of polyaromatic hydrocarbons and that structures possessing only aromatic sextets are especially stable, Figure . It has been shown that structures with the maximum amount of aromatic sextets for a given chirality and number of carbon atoms best describe the reactivity and geometry of CNTs and CNT–reactant studies. Accordingly, computational investigations employing “straight cut” CNT samples might misrepresent the reactivity of the studied model, which might be the source of some inconsistencies in published results on CNT–analyte interactions. For detailed discussions on the Clar sextet rule in CNTs, we refer the interested reader to key studies by Matsuo et al, Baldoni et al, , and Ormsby et al , …”
Section: Introduction and Scopementioning
confidence: 99%
“…It can be advantageous to truncate a surface for studying the properties of adsorbates [70][71][72][73][74][75][76], or for simulating the electron transport properties through molecules in a molecularjunction setup [77][78][79][80][81]. This is called a (truncated) cluster approach in this work.…”
Section: A Local Analysis Of Hybridization Functionsmentioning
confidence: 99%